Lateral shoot induction with exogenous 6-benzylaminopurine application at the vegetative growth stage in Phalaenopsis - Park, Ji Woo; Im, Nam Hyun; Lee, Hyo Beom (Horticulture, environment and biotechnology, 2025)
Phalaenopsis is a monopodial orchid, characterized by maintaining apical dominance throughout their life cycle. Branching or shoot induction can lead to the formation of more inflorescences and flowers that are associated with productivity in floricultural crops. This study was conducted to determine whether BAP (6-benzylaminopurine) treatment consistently induces lateral shoots and to compare the responses according to plant maturity, hybrid, and BAP concentrations. In Experiment 1, immature (3–4 leaves) and mature (6–7 leaves) plants were treated with 0 or 100 mg·L − 1 BAP. In Experiment 2, three hybrids (‘Mantefon’, ‘Flamingo’, and ‘Surf Song’) of mature (5–7 leaves) plants were treated with 0, 100, 200, or 400 mg·L − 1 BAP. Additionally, lateral shoots, apical shoots, and inflorescences were microscopically examined to compare their histological features. The results showed that exogenous BAP application could induce lateral shoots, and the lateral shoot induction rate and number tended to be higher in mature plants and at higher concentrations of BAP. The sensitivity of each hybrid to BAP varied slightly, with ‘Surf Song’ being the most sensitive among the hybrids tested. BAP treatment also increased the number of leaves. Microscopic observations confirmed that lateral shoots have vegetative meristems similar to apical shoots, rather than inflorescences, when they are first induced. In summary, BAP treatment of monopodial Phalaenopsis orchids can induce additional vegetative organs.